Texture and mineralogy of agates from the Triassic Fundy Basin, SE Canada and their linkage to eruptive events and syn-magmatic faulting - Georgia Pe-Piper; David J.W. Piper; Brian L. Hebert; Angeliki Papoutsa (Lithos, 2026)

The Dietary Inflammatory Index is Lower Among Healthy Older Adults Consuming a Walnut-Supplemented Diet. Ancillary Results from the Walnuts and Healthy Aging Randomized Controlled Trial - Lynnley Huey Stern; Jayme Brisco; Karen Jaceldo-Siegl; David Shavlik; Joan Sabate; Mercè Serra-Mir; Montserrat Cofán; Aleix Sala-Vila; Emilio Ros; Michael D. Wirth; James R. Hebert; Sujatha Rajaram (Journal of the Academy of Nutrition and Dietetics, 2026)

Submesoscale Eddy Spatiotemporal Variability Comparison Between Kuroshio Current and Open-Ocean Regions of the Western Pacific - Bryson Krause; Jackie May; Travis A. Smith; Joseph M. D’Addezio; David Hebert (Journal of Marine Science and Engineering, 2026)
This study examines the 3D attributes of submesoscale eddies identified over a 12-month period within the Western Pacific Ocean. Composite parameters of cyclonic submesoscale eddies (CSMEs) occurring within and away from the Kuroshio Current system are compared and analyzed for their surface and subsurface features, as well as the seasonality of their core properties. Within the Kuroshio Current (KC) region, CSMEs are faster, stronger and deeper than in the open water (OW) region, with composite eddy depths of 97.5 m and 77.5 m, or 2.8 and 2.0 times the mixed layer depth, respectively. Prominent dipolar divergence patterns both at the surface and at depth reveal the presence of ageostrophic influence, with KC CSME cores deviating 48% and OW CSMEs deviating 40% from geostrophic balance at the surface. This imbalance drives strong vertical motion with maximum upward velocities of 19.2 m day−1 at 57.7 m and 9.3 m day−1 at 157.1 m within the KC and OW region CSME cores, respectively. Subsurface extrema analysis reveals structural differences in CSMEs between dynamic regions. These results provide a useful model-based estimate for subsurface CSME features which are difficult to quantify with observations.

Accounting for Truncation Artifacts in Angiographic Perfusion - Kyle A. Lyman; Ryan M. Hebert; Charles C. Matouk; Kevin N. Sheth; Guido J. Falcone; W. Taylor Kimberly; David Y. Chung; Nils H. Petersen; Ona Wu (Translational Stroke Research, 2026)

Effects of pesticide use, microhabitat structure, and landscape diversity on arthropod communities, pest–disease dynamics, and yield in cacao agroecosystems - Bladimir Guaitero; Diego Fernando Cuero-Plaza; David Ricardo Hernández-Angarita; Hebert Camargo-Tamayo; Carolina Pisco-Ortiz; Edwin Rodríguez; Paola Zuluaga; Mario Porcel; Yeisson Gutiérrez (Agriculture, Ecosystems & Environment, 2026)

Closing the pollination gap in cacao agroforests: balancing pesticide use and shade management - Arledys Albino-Bohórquez; Bladimir Guaitero; David Ricardo Hernández-Angarita; Andrés Felipe Ramírez; Hebert Camargo; Yeisson Gutiérrez (Agroforestry Systems, 2026)

Oral selenium supplementation improves the reproductive performance of rams: A systematic review and meta-analysis - Alfonso Longinos Muñoz-Benitez; Rodolfo Vieyra-Alberto; Juan Hebert Hernandez-Medrano; José Luis Ponce Covarrubias; Erika Georgina Hernández-Rojas; David Alejandro Contreras Caro del Castillo; Juan Carlos Angeles-Hernandez (Small Ruminant Research, 2025)

Dispersant-enhanced photodissolution of macondo crude oil: A molecular perspective - David C. Podgorski; Jacob Walley; Matthew P. Shields; Deja Hebert; Maxwell L. Harsha; Robert G.M. Spencer; Matthew A. Tarr; Phoebe Zito (Journal of Hazardous Materials, 2024)

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Best practices for operating underwater gliders in Atlantic Canada - Nicolai von Oppeln-Bronikowski; Brad de Young; Melany Belzile; Adam Comeau; Frédéric Cyr; Richard Davis; Pamela Emery; Clark Richards; David Hebert; Jude Van Der Meer (Frontiers in Marine Science, 2023)
Ocean gliders are versatile tools for making ocean observations. This paper summarizes the experience, of nearly two decades, of glider observing activity in Atlantic Canada. It reviews key considerations for operating gliders based on the experience and the lessons learned. This paper has three main goals: 1. To provide new and emerging glider users with guidance and considerations for developing a glider program. 2. Review the literature on sensor development for gliders and the use of gliders. 3. To highlight different mission scenarios that include enough practical considerations to support operating gliders. The use of gliders is rapidly expanding, but the documentation and consolidation of best practices for their operational use in Atlantic Canada remains underdeveloped. This summary provides a guide that should be helpful both to new and experienced glider operators and potential users, to observe the oceanography of this region and addresses regional challenges. We believe documenting our experience will be also helpful to the global glider community. We summarize the most critical considerations of utilizing gliders. We review the issues specific to the platform use and concerns about how to optimize the use of key sensors to contribute to an oceanographic observing program.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Coenzyme Q10 Alleviates Chronic Nucleoside Reverse Transcriptase Inhibitor-Induced Premature Endothelial Senescence - Yi-Fan Chen; Valeria Y. Hebert; Krisztian Stadler; Stephen Y. Xue; Kate Slaybaugh; Elliot Luttrell-Williams; Mitzi C. Glover; David M. Krzywanski; Tammy R. Dugas (Cardiovascular Toxicology, 2019)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Polar Ocean Observations: A Critical Gap in the Observing System and Its Effect on Environmental Predictions From Hours to a Season - Gregory C. Smith; Richard Allard; Marcel Babin; Laurent Bertino; Matthieu Chevallier; Gary Corlett; Julia Crout; Fraser Davidson; Bruno Delille; Sarah T. Gille; David Hebert; Patrick Hyder; et al. (Frontiers in Marine Science, 2019)

Flower‐visitor communities of an arcto‐alpine plant—Global patterns in species richness, phylogenetic diversity and ecological functioning - Mikko Tiusanen; Tea Huotari; Paul D. N. Hebert; Tommi Andersson; Ashley Asmus; Joël Bêty; Emma Davis; Jennifer Gale; Bess Hardwick; David Hik; Christian Körner; Richard B. Lanctot; et al. (Molecular Ecology, 2019)
Pollination is an ecosystem function of global importance. Yet, who visits the flower of specific plants, how the composition of these visitors varies in space and time and how such variation translates into pollination services are hard to establish. The use of DNA barcodes allows us to address ecological patterns involving thousands of taxa that are difficult to identify. To clarify the regional variation in the visitor community of a widespread flower resource, we compared the composition of the arthropod community visiting species in the genus Dryas (mountain avens, family Rosaceae), throughout Arctic and high‐alpine areas. At each of 15 sites, we sampled Dryas visitors with 100 sticky flower mimics and identified specimens to Barcode Index Numbers ( BIN s) using a partial sequence of the mitochondrial COI gene. As a measure of ecosystem functioning, we quantified variation in the seed set of Dryas . To test for an association between phylogenetic and functional diversity, we characterized the structure of local visitor communities with both taxonomic and phylogenetic descriptors. In total, we detected 1,360 different BIN s, dominated by Diptera and Hymenoptera. The richness of visitors at each site appeared to be driven by local temperature and precipitation. Phylogeographic structure seemed reflective of geological history and mirrored trans‐Arctic patterns detected in plants. Seed set success varied widely among sites, with little variation attributable to pollinator species richness. This pattern suggests idiosyncratic associations, with function dominated by few and potentially different taxa at each site. Taken together, our findings illustrate the role of post‐glacial history in the assembly of flower‐visitor communities in the Arctic and offer insights for understanding how diversity translates into ecosystem functioning.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Diversity and bioprospection of fungal community present in oligotrophic soil of continental Antarctica - Valéria M. Godinho; Vívian N. Gonçalves; Iara F. Santiago; Hebert M. Figueredo; Gislaine A. Vitoreli; Carlos E. G. R. Schaefer; Emerson C. Barbosa; Jaquelline G. Oliveira; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; Silvane M. F. Murta; et al. (Extremophiles, 2015)

Biological invasions in soil: DNA barcoding as a monitoring tool in a multiple taxa survey targeting European earthworms and springtails in North America - David Porco; Thibaud Decaëns; Louis Deharveng; Samuel W. James; Dariusz Skarżyński; Christer Erséus; Kevin R. Butt; Benoit Richard; Paul D. N. Hebert (Biological Invasions, 2013)

Current concentrations and spatial and temporal trends in mercury in Great Lakes Herring Gull eggs, 1974–2009 - D. V. Chip Weseloh; David J. Moore; Craig E. Hebert; Shane R. de Solla; Birgit M. Braune; Daryl J. McGoldrick (Ecotoxicology, 2011)

Oceanographic Instrument Returns After Two Years - David Hebert; Tom Rossby (Oceanography, 2005)

Molecular physiology of cation-coupled Cl? cotransport: the SLC12 family - Steven C. Hebert; David B. Mount; Gerardo Gamba (Pflügers Archiv - European Journal of Physiology, 2004)

Fungal transformation of naphthalene - Carl E. Cerniglia; Richard L. Hebert; Paul J. Szaniszlo; David T. Gibson (Archives of Microbiology, 1978)